2014
DOI: 10.4040/jkan.2014.44.3.317
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Boys' and Girls' Families for Actor and Partner Effect of Stress, Depression and Parent-Adolescent Communication on Middle School Students' Suicidal Ideation: Triadic Data Analysis

Abstract: Purpose: This study was done to compare families of boys or of girls for actor and partner effect of stress, depression and parent-adolescent communication as perceived by mother, father and adolescent on adolescents' suicidal ideation. Methods: Participants were 183 families (104 boys' families, 79 girls' families) who met eligibility criteria. All measures were self-administered. Data were analyzed using SPSS 18.0 and AMOS 18.0 program. Results: In boys' families, boys' depression and communication with fath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…We found that the degree of perceived ease in sharing one’s concerns with their mother was significantly associated with fewer reports of depressive mood in school-attending adolescents. Our finding is consistent with that of a previous study, which found the quality of communication with a parent (mother for girls and father for boys) had effects on depression and suicidal ideation in adolescents [78]. Similarly, a recent longitudinal investigation of the social interaction–depressive mood association using growth curve modeling found an association between adolescent–parent communication (with father for boys and with mother for girls) and a decrease in depressive symptoms as the adolescents reached early adulthood [79].…”
Section: Discussionsupporting
confidence: 93%
“…We found that the degree of perceived ease in sharing one’s concerns with their mother was significantly associated with fewer reports of depressive mood in school-attending adolescents. Our finding is consistent with that of a previous study, which found the quality of communication with a parent (mother for girls and father for boys) had effects on depression and suicidal ideation in adolescents [78]. Similarly, a recent longitudinal investigation of the social interaction–depressive mood association using growth curve modeling found an association between adolescent–parent communication (with father for boys and with mother for girls) and a decrease in depressive symptoms as the adolescents reached early adulthood [79].…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have been conducted in recent decades to explore the factors associated with suicidal ideation among different populations [ 15 , 16 , 17 , 18 ] as well as the effects of environmental factors on suicide, such as the community and family environment [ 19 , 20 , 21 , 22 , 23 ]. Regarding environmental factors, relatives are closely connected to people’s lives, and their behaviors, experiences, and emotions could affect individuals’ mental health, which had been confirmed in previous studies [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Parent-child relationships, which are often evaluated by the quality of parent-child communication, conflict, and satisfaction, have been known to be a significant predictor of adolescent mental health (Quach et al, 2015). Parent-child communication is a direct and indirect risk factor in the mediation of adolescents' depression and suicidal ideation (Shin et al, 2014). Furthermore, parentchild conflict was significantly correlated with adolescents' problematic behaviors (Jang et al, 2014), and influences from the parent-child relationship continued throughout the adolescents' growth (Klahr et al, 2011).…”
Section: Introductionmentioning
confidence: 99%